2023
DOI: 10.7150/ijbs.81017
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid Perspective on Regulated Pyroptosis

Abstract: Pyroptosis is a novel pro-inflammatory cell programmed death dependent on Gasdermin (GSMD) family-mediated membrane pore formation and subsequent cell lysis, accompanied by the release of inflammatory factors and expanding inflammation in multiple tissues. All of these processes have impacts on a variety of metabolic disorders. Dysregulation of lipid metabolism is one of the most prominent metabolic alterations in many diseases, including the liver, cardiovascular system, and autoimmune diseases. Lipid metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 170 publications
0
3
0
Order By: Relevance
“…It is worth noting that lipid metabolism plays a crucial role in the generation of various bioactive lipid molecules, which serve as pivotal initiators and intrinsic regulators of pyroptosis. These bioactive lipid molecules have been found to facilitate pyroptosis by disrupting the intrinsic pathways involved in the production of ROS, endoplasmic reticulum (ER) stress, mitochondrial dysfunction, lysosomal disruption, and expression of associated molecules [ 58 ]. Recent research has demonstrated that the activation of NLRP3 inflammasome can induce lipid accumulation and pyroptosis in hepatocytes through the stimulation of free fatty acids [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that lipid metabolism plays a crucial role in the generation of various bioactive lipid molecules, which serve as pivotal initiators and intrinsic regulators of pyroptosis. These bioactive lipid molecules have been found to facilitate pyroptosis by disrupting the intrinsic pathways involved in the production of ROS, endoplasmic reticulum (ER) stress, mitochondrial dysfunction, lysosomal disruption, and expression of associated molecules [ 58 ]. Recent research has demonstrated that the activation of NLRP3 inflammasome can induce lipid accumulation and pyroptosis in hepatocytes through the stimulation of free fatty acids [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…External stimulus causing incomplete or incorrect protein folding in the ER leads to ER stress ( 134 ). Continuous or strong ER stress activates signaling pathways that result in cell damage or death ( 135 ). Recent reports indicate that ER stress is closely related to cell pyroptosis.…”
Section: Ros Regulates Pyroptosis In Other Diseasesmentioning
confidence: 99%
“…In general, ferroptosis has three essential features: (1) oxidation of PUFAs (including membrane phospholipids); (2) redox activities related to iron utilization; (3) loss of lipid hydrogen peroxide (LOOH) repair capacity [ 8 ]. Morphologically, ferroptosis cells exhibit typical changes in mitochondrial membrane shrinkage, reduction or disappearance of mitochondrial cristae, and rupture of the outer membrane, whereas mitochondria usually show swelling in other forms of cell death [ 39 , 40 , 41 ]. Furthermore, treated with the ferroptosis inducer erastin, the nuclei of cancer cells retained their structural integrity and no nuclear pyknosis or chromatin edge clustering was observed [ 42 ].…”
Section: Acsl4 In Ferroptosismentioning
confidence: 99%